Biocompatible complex coated with glycosaminoglycan for gene delivery. (21st April 2017) - Iwanaga, Marie; Kodama, Yukinobu; Muro, Takahiro; Nakagawa, Hiroo; Kurosaki, Tomoaki; Sato, Kayoko; Nakamura, Tadahiro; Kitahara, Takashi; Sasaki, Hitoshi
Abstract: The purpose of this study was to develop a ternary complex of plasmid DNA (pDNA) electrostatically assembled with dendrigraft poly-l -lysine (DGL) and biodegradable glycosaminoglycan for effective and secure gene delivery. High gene expression of pDNA/DGL complex was confirmed with slight cytotoxicity and erythrocyte agglutination. Anionic ternary complexes of 55.4–223.8 nm were formed by the addition of a glycosaminoglycan such as chondroitin sulfate A (CS-A), chondroitin sulfate B (CS-B), chondroitin sulfate C (CS-C) or hyaluronic acid (HA). Using the cell line B16-F10, most of the ternary complexes showed only weak gene expression and little cytotoxicity, although the pDNA/DGL/CS-A complexes maintained a certain level of gene expression. In particular, the pDNA/DGL/CS-A8 complexes showed significantly higher gene expression than pDNA/DGL complexes in the presence of fetal bovine serum. Gene expression from the pDNA/DGL/CS-A8 complex was inhibited by a high concentration of CS-A and endocytosis inhibitors. After intravenous administration of the pDNA/DGL/CS-A8 complex and the pDNA/DGL complex into ddY mice, high gene expression was observed in the reticuloendothelial systems, the pDNA/DGL/CS-A complex is expected to be useful for gene therapy.